Impact of intellectual capital on financial performance with company size moderation - Suhadi, Ilyas Alfian (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study aims to determine the effect of intellectual capital and company size on financial performance and the moderating role of company size on intellectual capital on the financial performance of state-owned companies in the infrastructure sector for the 2017-2022 period. Research methodology: This type of research is quantitative research that uses descriptive static methods, classical assumption tests, and hypothesis tests. In total, 42 samples were included in the study. Results: The results show that Intellectual capital has a significant positive effect on financial performance, while company size has a significant negative effect on financial performance. The company size in this study was not able to moderate intellectual capital to financial performance. Limitations: This study only used data from the IDX for 2017-2022 which allows data not to be obtained in detail. The sample in this study uses only infrastructure sector companies that use rupiah currency.   Contribution:  This study reveals that intellectual capital has a positive and significant effect on financial performance, whereas company size does not moderate this relationship, providing important insights for the management of intellectual capital and strategy for state-owned companies in the infrastructure sector. Novelty: Company size is used as a moderating variable because it is thought to be able to support the company's operational activities in supporting the management of its resources.